Relation between kinematic analysis of wheelchair propulsion and wheelchair functional basketball classification - Crespo-Ruiz, B. M.; del Ama-Espinosa, A. J.; Gil-Agudo, A. M. (Adapted Physical Activity Quarterly, 2011)
The objective was to conduct a methodological pilot study to analyze wheelchair propulsion upper limb kinematics in standard competitive play considering the functional classification of each athlete. Ten basketball players with a functional classification ranging from 1 to 4 were included in the study. Four camcorders (Kinescan-IBV) and a treadmill for wheelchairs were used. Temporal parameters were analyzed and the upper limb kinematics was obtained using ISB recommendations. The value of the temporal parameters such as push phase duration, the ratio of push phase/recovery phase, contact, and propulsion angle seems to reduce as the functional classification increases. A methodological protocol has been developed that allows the analysis of kinematic characteristics of wheelchair propulsion in basketball players taking into account their functional classification.